ANALISIS PROKSIMAT FAMILY TURBINIDAE DI PERAIRAN PANTAI DESA LATUHALAT - Salmanu, Sriyanti I. A.; Liline, Sintje; Ubra, Christo (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: The coastal waters of Latuhalat village have a fertile rocky substrate with various marine biota that live in these coastal waters. Among them are the moon-eyed snail (Turbo chrysostumus, L.) and the cat-eye snail (Turbo smaragdus, Gmelin, 1791). Snail meat in coastal waters is thought to contain high nutritional value as well as moon eye snail (Turbo chrysostumus, L.) and cat eye snail (Turbo smaragdus, Gmelin, 1791). Because it is suspected to have a high nutritional content, this snail meat is favored by the public. However, information about its nutritional content is not yet available. Thus, this study aims to determine the nutritional value or chemical composition of the family Turbinidae snail. Methods: Laboratory analysis to determine the nutritional value (proximate) with the method: proximate (AOAC 2005), which was analyzed at the Testing, Calibration and Certification Services Laboratory Unit, ITB, Bogor. Results: Based on the results of proximate analysis of the tubinidae family found in the coastal waters of Latuhalat village, the results obtained are, water content is 20.73%, fat content is 2.21%, protein content is 58.38%, ash content is 15.69%, fiber 2.29%, carbohydrates 2.99% . Conclusion: Based on the results of the research conducted, the conclusion that can be drawn in this study is that the protein content of the Turinidae family is quite high, namely 58.38% and the low fat content of 2.21%, the Turinidae family can be used as a source of animal protein for fulfillment the body's energy needs.